تنمية الذكاءات المتعددة من منظور تربوي إسلامي: Developing multiple intelligences from an Islamic educational perspective - Fadhli, Sarah Adel; Mohamed Adnan, Mohamed Azrien; Wan Mokhtar , Wan Rohani (Online Journal of Research in Islamic Studies, 2021)
Islam as an educational approach has received great attention, as the nucleus of societies, and in its perpetuation as the perpetuation of human life, Islam is a minimum and last religion, which has come to promote human behavior and belief, and for man to develop a useful omen for his society and nation, taking into account human emotions, human energy, physical impulses, and psychological concepts in the development of his multiple flavors ( This study comes to answer the president's question: What is the Islamic tendency to develop multiple intelligence in the field of education?. The study will aim to achieve a range of objectives, including the further identification of the concept of Islamic education, the diagnosis of multiple intelligence, and the identification of the extent to which Islamic education will contribute to the development of multiple intelligence. This will be done by the methodology of description, analysis, and assimilation through a group of investigators containing the variables of the study, namely, Islamic education and the development of multiple intelligence.